Forage seed production and management techniques - Assefa, Getnet; Mekonnen, Kindu; Gebreyes, Million; Bezabih, Melkamu; Adie, Aberra; Seifu, Haimanot (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Despite the large number of recommended and registered forage crop varieties and species for the different agro-ecologies of Ethiopia and critical feed shortage revealed by the very poor livestock productivity, adoption and use of cultivated forage crops in the country is still low. Some of the reasons indicated are inadequate quantity and quality seed supply, lack of technical skills, low seed productivity of forages especially perennial grasses and legumes and poor and subsistence production and none market oriented production systems. These calls to look into the status of the Ethiopian forage seed system, identify the major constraints and enhance forage seed production to improve the seed supply system in the country. The objective of this brief is to give an overview of forage seed systems and recommend major seed production practices in Ethiopia.